Evaluation of Ishiofemoral Space and Quadratus Femoris Space by Magnetic Resonance Imaging - Kutsi Tuncer; Gökhan Polat; Adem Karaman; Sinan Yılar; Fatih Alper (Van Tıp Dergisi, 2019)
INTRODUCTION: We aimed to evaluate the ishiofemoral (IF) space and quadratus femoris (QF) space by magnetic resonance imaging in a Turkish population. METHODS: A total of 488 magnetic resonance images of the hip were evaluated by one radiologists to measure IF and QF distances. The data were grouped according to gender and side (right / left) and statistically compared. RESULTS: The median value of the IF and QF space width was 25.00 (95% CI; 23.00 to 27.00) and 20.00 (95% CI; 17.00 to 22.00), respectively. There was no significant difference between the left and right side in terms of IF and QF distance (p = 0.99, p = 0.92) (Table 1), but a significant difference was found between male and female patients (p < 0.0001, p < 0.0001, respectively) (Table 1). DISCUSSION AND CONCLUSION: In the Turkish population investigated, the IF and QF distance was lower in women than in men. Therefore, the risk of impingement is considered to be higher in the female population.